«Fiere vicende dell'età di mezzo» Studi per Gian Maria Varanini - Guglielmotti, Paola; Lazzarini, Isabella (Reti Medievali E-Book, 2021)
With the present Festschrift written in times of pandemic, the authors wish to honour and thank Gian Maria Varanini, paying tribute to him on the occasion of his retirement from the University. Varanini is a great scholar, sustained by an inexhaustible passion for history in all its dimensions, from the most minute to the most universal, and by a sensitive and critical attention to the interpretation of historical phenomena that has been provided by successive generations of scholars. A generous cultural organiser and an excellent publisher and editor, as an academic and professor he has always been committed to the safeguard of historical disciplines. Papers of E. Artifoni, S. Carocci, G. Castelnuovo, P. Corrao, M.N. Covini, M. Della Misericordia, F. Del Tredici, M. Gentile, P. Grillo, P. Guglielmotti, I. Lazzarini, J.-C. Maire Vigueur, E.I. Mineo, G. Petralia, L. Provero, R. Rao, F. Senatore, L. Tanzini, M. Zabbia.